A sub-freshness monitoring chitosan/starch-based colorimetric film for improving color recognition accuracy via controlling the pH value of the film-forming solution. (15th September 2022) - Li, Bin; Bao, Yiwen; Li, Jiaxin; Bi, Jinfeng; Chen, Qinqin; Cui, Huijun; Wang, Yuxuan; Tian, Jinlong; Shu, Chi; Wang, Yuehua; Lang, Yuxi; Zhang, Weijia; et al.
Graphical abstract: Highlights: The undistinguishable colorimetric endpoint of chitosan-based films was solved. Film's initial color was significantly affected by pH of the film-forming liquid. The colorimetric film has high response sensitivity to ammonia gas. The colorimetric film's color change is significant in the pH range of 4–8. The colorimetric film realizes the whole-process monitoring of shrimp freshness. Abstract: The demand for intelligent packaging in food sub-freshness monitoring is increasing. Herein, a pH and NH3 responsing colorimetric film (PS-CH-LCA) was fabricated based on potato starch (PS), chitosan (CH) and Lonicera caerulea L. anthocyanins (LCA) via controlling the pH value of the film-forming solution, and was applied to the real-time monitoring of shrimp freshness. The PS-CH-LCA pH 2.5 film exhibited the highest tensile strength (6.43 MPa), the lowest water solubility (33.11%) and the most sensitive color responsiveness. Morphological and structural results revealed that CH was attached to the surface of PS via hydrogen bond, and anthocyanins were well immobilized in the film-forming matrix. The sensitive color change and its high correlation with spoilage indices demonstrated the PS-CH-LCA pH 2.5 film well indicated fresh, sub-fresh, spoiled level of shrimp. The results solved the limitation of chitosan-based packaging films in undistinguishable colorimetric endpoints, providing a new strategy for indicating the sub-freshness of food packaging.